Archives: Unfolding architectural narratives - Bianco Sommer, Julia; Bruce, Irma (My University, 2024)
With a fascination for the act of drawing, this thesis focuses on using unconventional methods to uncover and investigate architectural narratives, exposing layers embedded within our built environment to introduce a transformation formed by iterations of reality. The narrative unfolds by using the industrial complex of Rosenlundsverket as a catalyst. As the industry faces liquidation, questions about the building’s future emerge. The start of the process takes on a more conventional way of approaching an existing building, where the building is viewed as an object to portray. This journey is physically manifested in the creation of hand drawings that encapsulate the investigative findings. Drawing serves as more than just a communication tool; it becomes a dynamic medium where representation and design intricately intertwine, allowing us to discover the dimension of reality and imagination. Through this process it made us think if the existing building could be seen as more than an object, and what would the outcome be if we saw it as the subject, a source for inspiration to compose a design transformation. The method is structured into three stages: The Observer, The Intepreter and, The Actor. These perspectives are created to depict the process, and to develop a deeper understanding of each iteration. The thesis compasses the development of archives and a speculative design, by re-imagining and re-articulating the essence of Rosenlundsverket. Developing a method that allows for a process that does not kill intuitions by rationalizing. By drawing Rosenlundsverket as a carrier of components, the thesis unfolds diverse design methodologies to enable innovative approaches, allowing for an introduction of speculative design aimed at questioning conventional notions of value. The outcome has taken shape of drawings and models. We have come to understand that art and architecture are not static entities but dynamic processes. This insight imprints the research of our journey, inviting further exploration and question architectural narratives. Resulting in twelve hand drawings (700 x 1000 mm), representing each stage of our process.
Keywords: Architectural narratives, Iterations of reality, Perception of architecture, Speculative design, Drawing as medium